Merkel Cell Carcinoma of the Head and Neck: A Single Institutional Experience - G. Morand; D. Vital; T. Pézier; D. Holzmann; M. Roessle; A. Cozzio; G. F. Huber (Journal of Skin Cancer)
Merkel cell carcinoma (MCC) is a rare cutaneous malignancy occurring mostly in older immunocompromized Caucasian males. A growing incidence of MCC has been reported in epidemiological studies. Treatment of MCC usually consists of surgical excision, pathological lymph node evaluation, and adjuvant radiotherapy. This paper reports the experience of a single tertiary center institution with 17 head and neck Merkel cell carcinoma patients. Median followup for the cohort was 37.5 months. After five years, recurrence-free survival, disease specific survival, and overall survival were 85%, 90%, and 83%, respectively. Our limited data support the use of adjuvant radiotherapy. We also report two cases of MCC located at the vestibule of the nose and two cases of spontaneous regression after diagnostic biopsy. About 40% of our patients were referred to our center for surgical revision and pathological lymph node evaluation. Increased awareness of MCC and an interdisciplinary approach are essential in the management of MCC.